MMB Self-Determination and Rights of Minorities: Good or Bad for them? - Belihu, Mezgebu Mandefro (International Journal of Law, Human Rights and Constitutional Studies; Vol 6 No 2 (2024): International Journal of Law, Human Rights and Constitutional Studies, 2024)
Abstract This study entitled “Self-Determination and Minority Rights: Good or bad for them?”, is based on theoretical and legal analysis of the nexus between the concepts and as such it does not extends to the practical cases and specific examples of certain area or country. Hence, an attempt has been made to conceptualize the term minority and its defining features. Secondly, it addressed the question of whether minorities can claim the right to self-determination or not. Thirdly, it dealt with the question of whether self-determination is good or bad for minorities. To address the questions and construct this essay, survey of the literature is primarily employed to support my reading of books and journals. Secondly, analysis of law and personal experience is employed to construct this essay. This study has concluded that, since minorities are an important unit of the people of nations, self determination has an important role in advancing the other rights of minorities. By claiming the right to self-determination, minorities determine their political, economic, social and cultural destiny and at last preserve their separate identity.